Isolation and Characterization of an HLA-DPB1*04: 01-restricted MAGE-A3 T-Cell Receptor for Cancer Immunotherapy. Issue 5 (June 2016) - Yao, Xin; Lu, Yong-Chen; Parker, Linda L.; Li, Yong F.; El-Gamil, Mona; Black, Mary A.; Xu, Hui; Feldman, Steven A.; van der Bruggen, Pierre; Rosenberg, Steven A.; Robbins, Paul F.
Abstract : Long-term tumor regressions have been observed in patients following the adoptive transfer of autologous tumor-infiltrating lymphocytes or genetically modified T cells expressing MHC class I-restricted T-cell receptors (TCRs), but clinical trials have not evaluated responses to genetically modified T cells expressing antitumor MHC class II-restricted TCRs. As studies carried out in a murine tumor model system have demonstrated that the adoptive transfer of CD4 + T cells could lead to the regression of established tumors, we plan to test the hypothesis that CD4 + T cells can also induce tumor regressions in cancer patients. In this study, 2 MAGE-A3-specific TCRs were isolated from a regulatory T-cell clone (6F9) and an effector clone (R12C9), generated from the peripheral blood of 2 melanoma patients after MAGE-A3 vaccination. The results indicated that T cells transduced with 6F9 TCR mediated stronger effector functions than R12C9 TCR. The 6F9 TCR specifically recognized MAGE-A3 and the closely related MAGE-A6 gene product, but not other members of the MAGE-A family in the context of HLA-DPB1*04:01. To test the feasibility of a potential clinical trial using this TCR, a clinical-scale procedure was developed to obtain a large number of purified CD4 + T cells transduced with 6F9 TCR. Because HLA-DPB1*04:01 is present in ∼60% of the Caucasian population and MAGE-A3 is frequently expressed in a variety of cancer types, this TCR immunotherapy could potentially be applicable for a significant portion of cancer patients. Abstract : Supplemental Digital Content is available in the text.